2020
DOI: 10.1177/1362361320921040
|View full text |Cite
|
Sign up to set email alerts
|

Tell me where it is: Selective difficulties in spatial language on the autism spectrum

Abstract: Proficient use of spatial terms such as under, to the left of or in front of is a central component of daily communication and is important in the development of language and spatial cognition. Here we examine spatial language abilities in intellectually high-functioning individuals with autism spectrum disorder, an area previously overlooked in autism research. Twenty-five high-functioning individuals with ASD and 25 typically developing controls, matched for chronological age and cognitive abilities, complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…This finding aligns with prior work suggesting diminished use of language in the form of verbal mediation as a strategy during visuospatial task performance (Larson et al, 2021;Williams et al, 2012). Our finding that structural language competence was associated with mental rotation accuracy, however, may provide broad support for studies indicating cross-domain associations between language and spatial cognition at different levels of granularity and targeting different levels of language structure (e.g., Bochynska, Coventry et al, 2020;; but see Prescott et al, 2023).…”
Section: Mental Rotation and Language In Asdsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding aligns with prior work suggesting diminished use of language in the form of verbal mediation as a strategy during visuospatial task performance (Larson et al, 2021;Williams et al, 2012). Our finding that structural language competence was associated with mental rotation accuracy, however, may provide broad support for studies indicating cross-domain associations between language and spatial cognition at different levels of granularity and targeting different levels of language structure (e.g., Bochynska, Coventry et al, 2020;; but see Prescott et al, 2023).…”
Section: Mental Rotation and Language In Asdsupporting
confidence: 89%
“…Visuospatial skills are often viewed as a relative strength in autism spectrum disorder (ASD), yet difficulties have been observed on visuospatial executive function (Lai et al, 2017; Wang et al, 2017) and spatial navigation tasks (Lind et al, 2013, 2014; Ring et al, 2018; Smith, 2015), as well as in the comprehension and production of spatial language (Bochynska, Coventry et al, 2020; Bochynska, Vulchanova et al, 2020; but see Prescott et al, 2023). Development of spatial cognition and language is thought to be interrelated through several mechanisms in neurotypical (NT) development, including engagement of shared concepts between systems (e.g., spatial verbs and syntactic frames, spatial prepositions and directional information; Coventry & Garrod, 2004; Hayward & Tarr, 1995; Landau & Hoffman, 2005; Landau & Sciences, 1993) and the use of verbal mediation to guide behavior (e.g., self‐talk; Larson et al, 2021; Marcovitch & Zelazo, 2009; Zelazo, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As many theorists have argued, the deficits in metaphor processing for people with autism may be closely linked to more general deficits in linguistic skills. For example, even though autistic individuals are generally unimpaired in spatial skills, they show deficits in the use of spatial language (Bochynska, Coventry, Vulchanov, & Vulchanova, 2020), and the integration of materials presented in different modalities (for example, pictorial and verbal) might pose a particular challenge for them (cf. Kalandadze et al, 2019).…”
Section: Relations Between Metaphor Processing Analogical Reasoning A...mentioning
confidence: 99%
“…Participants suggested that using the correct terminology for body parts is vital as it could identify safeguarding concerns such as sexual abuse. There is a particular dependency on teachers in this regard as autistic learners may not be able to effectively communicate concerning this topic (Bochynska et al, 2020). Additionally, learners may not even be aware of what a safeguarding scenario is if they have not been educated on it; highlighted by Kathleen that it is "easy" for autistic individuals to be sexually abused.…”
Section: Theme 1: Pedagogical Restrictionsmentioning
confidence: 99%